Особенности применения теплоустойчивых сталей для паропроводов и элементов их систем - Гаращенко, Елена Сергеевна (Национальный технический университет "Харьковский политехнический институт", 2019)
Представлены особенности использования теплоустойчивых сталей 12Х1МФ, 15Х1М1Ф, 12Х2МФСР и др. для изготовления элементов паропроводов тепловых электростанций, выработавших свой парковый ресурс, что в настоящее время является актуальной задачей. В работе выявлены причины возникновения повреждаемости и снижения эксплуатационных характеристик металла сварных соединений труб и паропроводов, представлены результаты изучения структуры и механических свойств сварных соединений паропроводов, а также выявлены причины возникновения локальной концентрации напряжений в металле.

Power generating units of heat and power plants equipped with steam boilers that have supercritical and high steam parameters and the system of steam pipelines produce the major portion of electric power in Ukraine. This scientific paper describes the peculiarities of the use of heat-resistant pearlitic steels of 12Х1МF, 15Х1М1F, 12Х2МFSR grades and others. These steels are used to manufacture the elements for the steam pipelines of thermal power plants whose service life has already run out and it is a vital problem at the moment. This scientific paper looks into the reasons for the appearance of damages and degraded operating performances of the welded pipe junctions of steam pipelines. The research data obtained during the studies of the structure and mechanical properties of the welded junctions of steam pipelines have been given. Consideration was given to the factors that affect welded junctions during their long-term operation. It was established that the welded junctions made of heat-resistant pearlitic steels degrade during their long-term operation following the creep crack formation mechanism. It was established that the welded junctions of steam pipelines with the accrued operating time of 270.000 hours and an increased number of the start-stop cycles of power generating units are characterized by an increased probability of faults following the fatigue mechanism. It depends to a great extent on the local concentration of stresses in the structures of welded junctions and their structural state.
Peculiarities of the use of heat-resistant steels for steam pipelines and the elements of their systems
Keywords: сварные соединения; повреждаемость; термообработка; зона термического влияния; welded junctions; fault probability; thermal treatment; heat-affected zone